2005
DOI: 10.1161/01.atv.0000190608.28704.71
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Ubiquitin Proteasome Pathway Gene Expression in Skeletal Muscle With Exercise and Statins

Abstract: Objective-Statins are safe medications but have side effects including myalgia and rhabdomyolysis. How statins provoke muscle damage is not known, but this effect is exacerbated by exercise. Methods and Results-Healthy subjects took Atorvastatin (80 mg/daily) or placebo for 4 weeks. Biopsies of both vastus lateralis muscles were performed 8 hours after eccentric exercise (known to result in muscle soreness and damage) of the left leg at baseline and the right leg after statin/placebo treatment. Gene expression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
90
1
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 118 publications
(98 citation statements)
references
References 36 publications
6
90
1
1
Order By: Relevance
“…In the other hand, the percent of the caspase 3-immuno positive muscle fibers increased with higher doses. This was in agreement with the study of Mazroa and Asker, [19] who observed the expression of active caspase 9 in rat skeletal muscle after 10 mg/kg of atorvastatin treatment and the study of Urso et al, [40] who found that atorvastatin induces apoptosis in the skeletal muscle at a genetic level. Different statins can induce apoptosis in skeletal muscle [41].…”
Section: The Morphometric Resultssupporting
confidence: 93%
“…In the other hand, the percent of the caspase 3-immuno positive muscle fibers increased with higher doses. This was in agreement with the study of Mazroa and Asker, [19] who observed the expression of active caspase 9 in rat skeletal muscle after 10 mg/kg of atorvastatin treatment and the study of Urso et al, [40] who found that atorvastatin induces apoptosis in the skeletal muscle at a genetic level. Different statins can induce apoptosis in skeletal muscle [41].…”
Section: The Morphometric Resultssupporting
confidence: 93%
“…In skeletal muscle tissue statin therapy can cause mitochondrial dysfunction limited typically to complex I of the respiratory chain, which increases mitochondrial NADH and the intracellular redox potential (NADH/NAD + ratio), activates pyruvate dehydrogenase kinase (PDK), and inhibits flux via the pyruvate dehydrogenase complex (PDC) [81,82]. Another possible mechanism for statin-induced myopathy during exercise might be the down-regulation of atrogin-1 gene expression, a critical component of the ubiquitin proteasome pathway and of muscle protein catabolism [83]. Inflammation, exercise-induced irisin secretion, a myokine modulating the impact of exercise on adipocyte browning, reduced sarcolemmal or endoplasmic reticulum cholesterol, depletion of intracellular cholesterol leading to increased calcium influx, increased myocellular concentrations of cholesterol and plant sterols, modified signal transduction and metabolism due to decreased mevalonic acid and its metabolite concentrations as well as vitamin D deficiency or coenzyme Q10 deficiency might also increase the probability of statin therapy influence on the capacity of skeletal muscle to conform to the stress of exercise training [84,85].…”
Section: Physical Activity and Statin Intolerancementioning
confidence: 99%
“…We know that, the ubiquitinproteasome-dependent proteolytic pathway (UP pathway) is responsible for the breakdown of long-lived myofibrillar proteins (e.g., actin, myosin and troponin) in skeletal muscle, which releases of myoglobin. Statin may upregulate skeletal muscle gene expression of UP pathway [11]. Mechanisms of rhabdomyolysis induced acute kidney injury are renal vasoconstriction secondary to excessive leakage of extracellular fluid into the damaged muscle cells, formation of intratubular myoglobin casts that induce intra-tubular obstruction and direct toxin-related tubular damage [12].…”
Section: Discussionmentioning
confidence: 99%